Trade and Insurance With Imperfectly Observed Outcomes - Dixit, Avinash (Quarterly Journal of Economics, 1989)
Journal Article Trade and Insurance with Imperfectly Observed Outcomes Get access Avinash Dixit Avinash Dixit Princeton University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 104, Issue 1, February 1989, Pages 195–203, https://doi.org/10.2307/2937842 Published: 01 February 1989